(untitled) (Economic and Political Thought, 2019)
The name Benelux is a commonly known abbreviation of the European organisation formed by three states: the Kingdom of Belgium, the Kingdom of the Netherlands and the Duchy of Luxemburg. The Benelux Union started in 1944 as a tariff union, which was finalised by a treaty establishing the Benelux Economic Union in 1958. The new Benelux Treaty was signed on 17 June 2008 in The Hague. Since then, the cooperation has been focused on the following main areas: the internal and the economic union market, sustainable development, justice and internal affairs. The mission of Benelux is the best possible cooperation between the member states and ensuring the welfare of the citizens of Belgium, the Netherlands and Luxemburg. After Poland’s accession to the European Union, Polish politicians’ interest in the functioning of the Benelux states decreased although the present democratic Poland’s governments use the common achievements of all its member states. Polish governments’ foreign policy towards the Benelux states is at present carried out within the Visegrad Group in the V4+ (plus) format. On 19 June 2017, after 16 years’ break, the Visegrad Group and Benelux states’ Prime Ministers met in Warsaw. The debate on the future of the European Union was the impulse to return to talks at the prime ministers’ level. Actually, two issues divide the V4 and the Benelux states. The Benelux Union states are for the quota solution, which the V4 states oppose. The issue of the European integration within the ‘multi-speed idea’ constitutes another division line. As far as this is concerned, there are differences within the V4 but most members are against it. The Visegrad – Benelux cooperation nowadays consists in attempting to form coalition with the Benelux states in the EU voting in order to achieve trans-regional agreements. The experience prescribes maintaining scepticism about predicting agreements between the Czech Republic, Hungary and Poland and the Netherlands, Belgium, Luxemburg and Slovakia. The meeting in Warsaw proved that the debate on the future of the European Union to a great extent would first take place in regional groups and then formally in the EU forum.